El embarazo y el desarrollo educativo de las estudiantes de tercero de bachillerato de la unidad educativa San Francisco de Asís, provincia de Zamora - VALDIVIEZO AGUILAR, YAIRA LIDIBETTE (2024)
This study analyzes how teenage pregnancy affects the educational development of third year students at the San Francisco de Asis Educational Unit, Zamora. To analyze the causes of pregnancy and its impact on the academic performance of adolescents. An inductive approach was used with student surveys. Ninety-one percent believe that the lack of information on sexual health increases adolescent pregnancies, and 36% believe that pregnant students receive good educational attention. Twenty-nine percent feel unsupported by the educational community, revealing the need for improved resources and programs. Pregnancy decreases students' self-esteem and motivation, affecting their academic performance. The findings underscore the need for interventions for pregnant students and improved sexual health education to reduce adolescent pregnancy. It is crucial to create an inclusive educational environment that allows young women to continue their education and graduate successfully. Therefore, it highlights the need for educational policies on teenage pregnancy and its effect on school.